2017
DOI: 10.1074/jbc.m117.803346
|View full text |Cite
|
Sign up to set email alerts
|

The MukB–topoisomerase IV interaction is required for proper chromosome compaction

Abstract: The bacterial condensin MukB and the cellular decatenating enzyme topoisomerase IV interact. This interaction stimulates intramolecular reactions catalyzed by topoisomerase IV, supercoiled DNA relaxation, and DNA knotting but not intermolecular reactions such as decatenation of linked DNAs. We have demonstrated previously that MukB condenses DNA by sequestering negative supercoils and stabilizing topologically isolated loops in the DNA. We show here that the MukB-topoisomerase IV interaction stabilizes MukB on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…3 b ii). Recently, it was found that the MukB-TopoIV interaction at origins in fact promoted DNA condensation and did not involve any catalytic activity of TopoIV 28 . It may therefore be that TopoIV bound to MukB at origins does not contribute to resolution of precatenanes, but instead has other roles.…”
Section: Discussionmentioning
confidence: 99%
“…3 b ii). Recently, it was found that the MukB-TopoIV interaction at origins in fact promoted DNA condensation and did not involve any catalytic activity of TopoIV 28 . It may therefore be that TopoIV bound to MukB at origins does not contribute to resolution of precatenanes, but instead has other roles.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated cultures of strains CL109, CL113, and CL281 were diluted to an optical density at 600 nm (OD 600 ) of 0.01 and grown at either 37°C (when CL109 and CL113 were compared) or 30°C (when CL109 and CL281 were compared) in M9 minimal medium supplemented with 20 g/ml each of thiamine, thymine, and uracil and either 0.2% glucose (for the comparison of CL109 and CL113) or 0.2% glycerol (for the comparison of CL109 and CL281) to an OD 600 of 0.1. Cells were viewed on grooved 4% agarose (NuSieve GTG; Lonza) pads prepared in 1ϫ phosphatebuffered saline (PBS) as described previously (57). Cells were imaged in the phase, Texas Red, and GFP channels in three consecutive 0.2-m Z-planes using a Nikon Eclipse Ti microscope with an Plan Apo 100ϫ/1.40-numerical-aperture objective and an Andor Neo CMOS camera enclosed in an Okolab environmental chamber held at the indicated temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…Besides its role in chromosome segregation, topoisomerase IV was also proposed to aid MukBEF complex in chromosome condensation. Recent data suggest that topoisomerase IV can stabilize the MukB homodimer on the DNA, and thus enhance compaction of DNA [ 105 ]. Interestingly, the same study shows that even catalytically inactive ParC subunit of topoisomerase IV is able to promote MukB driven compaction.…”
Section: Regulation Of Topoisomerase II Activity: Guidance By the mentioning
confidence: 99%